1990
DOI: 10.1084/jem.171.5.1649
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo modification of Neisseria gonorrhoeae lipooligosaccharide epitope structure by sialylation.

Abstract: Previous studies have shown that human serum, guinea pig and human red cells, and human white cells contain low and high M, substances that induce gonococcal strains to become serum resistant (1-4) and change lipooligosaccharide (LOS)' pattern (5, 6) . In more recent studies, the same investigators have shown that the low Mr substance in-blood is cytidine monophospho-N-acetylneuraminic acid (CMP-NANA) or a related compound (7,8) . These studies suggest that in vivo, sufficient concentrations of CMP-NANA might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
137
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 51 publications
4
137
0
Order By: Relevance
“…Gonococci with sialylated LOS are resistant to C-mediated lysis and less susceptible to C-dependent phagocytosis (45). In meningococci, both the capsule and LOS are important factors for serum resistance (36,46).…”
Section: Discussionmentioning
confidence: 99%
“…Gonococci with sialylated LOS are resistant to C-mediated lysis and less susceptible to C-dependent phagocytosis (45). In meningococci, both the capsule and LOS are important factors for serum resistance (36,46).…”
Section: Discussionmentioning
confidence: 99%
“…Neuraminidase treatment of antigens on EIA plates was done essentially as described previously (19)(20)(21). The EIA plates were coated with LPS (25 g/ml of PBS) or with 100 l of a bacterial suspension (unheated; A 595 Ï­ 0.2) in PBS.…”
Section: Ii) De-o N Acylation Of Lps By Strong Alkali Treatment (Ps-mentioning
confidence: 99%
“…This tetraose is the carbohydrate moiety also found in a human glycosphingolipid, paragloboside (8,11). Furthermore, in vitro experiments showed that gonococci utilize exogenous cytidine monophospho-N-acetylneuraminic acid and sialylate their LOS (17). As a result of sialylation, gonococci become resistant to complement-mediated killing (15,16).…”
mentioning
confidence: 99%
“…In addition to complex LOS expression, studies by us and others (8,11) have shown that gonococci may mimic human glycolipids or may change serum sensitivity by modifying their LOS (15)(16)(17). The 4.5-kDa LOS produced by strain F62 contains a lactoneotetraose moiety that is linked to the Hep [1] residue of the core trisaccharide as described above (11).…”
mentioning
confidence: 99%